Pharmacokinetics of the Proton Pump Inhibitor CDRI-85/92 and its Ester Prodrug, a New H+/K+-ATPase Inhibitor with Anti-ulcer Activities, after Oral Doses in Rats - Lal, Jawahar; Pandey, Shailendra Kumar; Dikshit, Dinesh Kumar; Gupta, Ram Chandra (Arzneimittelforschung, 2009)
5-Styryl-4,5-cis-1,3-oxazole-2-one-4-car-boxylic acid (CDRI-85/92) is a new proton pump inhibitor presently in advanced stage of preclinical trials as antiulcer pharmacophore. Since proton pump inhibitors are prodrugs requiring activation in acid environment, an ester prodrug of CDRI-85/92 was also synthesized. In view of the importance, a pharmacokinetic study of CDRI-85/92 and its ester prodrug was conducted after oral doses in rats. Following a 20 mg/kg oral dose of CDRI-85/92, the compound was detectable in the serum samples up to 24 h with a maximum serum concentration (Cmax) of 1 838.40 ± 101.16 ng/ml at 1.5 h and an elimination half-life of 4.96 h, whereas, multiple Cmax values of CDRI-85/92 were observed with oral doses (equivalent to 20 mg/kg of CDRI-85/92) of the ester prodrug of the compound. All the three Cmax values of the compound were lower than that after oral dose of CDRI-85/92. The compound was eliminated slowly from serum with an elimination half-life of 5.14 h. Moreover, the systemic availability of CDRI-85/92 also decreased from 6111 to 3 463 ng · h/ml after the ester prodrug administration. The decrease in systemic availability of CDRI-85/92 could be due to its higher clearance after its ester prodrug administration.
Keywords: CDRI-85/92, HPLC, pharmacokinetics, prodrug, rat; Proton pump inhibitor; 5-Styryl-4,5-cis-1,3-oxazole-2-one-4-carboxylic acid